Prevalence and Risk Factors of Hypertension in Adults in an Urban Slum, Tirupati, A.P. - Reddy S; Prabhu G (Indian Journal of Community Medicine, 2005)
Research question : What is the prevalence of hypertension and its risk factors among adults aged 20-60 years residing years residing in an urban slum area of Tirupati town, A.P.? Objective : To study the prevalence of hypertension and its risk factors as well as its extent of diagnosis and management among adults aged 20-60 years residing in an urban slum area of Tirupati. Study design : Cross sectional. Study setting : Channa Reddy Colony (Urban slum area) in Tirupati town, A.P. Study subjects : 1000 adults in the age group of 20-60 years (Males-500; Females-500) residing in an urban slum area of Tirupati town, A.P. Study variables : Age, sex, occupation, family history of hypertension, history of cerebrovascular/cardiovascular events, diabetes mellitus, saturated fat intake, intake of excess salt, smoking, alcohol intake and regular physical exercise. Outcome Variables : Number of hypertensives and mean blood pressure level estimations. Statistical analysis : Proportions, Chi--square tests, ′F′ ratios, ′t′ tests, Odds ratios and 95% confidence intervals. Results : The overall prevalence of hypertension was found to be 8.6%. Out of the 86 hypertensives, 72 (83.7%) were aware of their hypertension; all of those aware were under treatment; among the treated, only 30 (41.7%) had satisfactory control of their hypertension. Higher prevalence of hypertension was found with history of cerbrovascular/cardiovascular events (50.0%), diabetes mellitus (33.3%), family history of hypertension (23.3%), smoking (22.4%), age more than 50 years (22.2%), alcohol intake (20.0%), lack of physical exercise (15.8%), B.M.I.>25 (14.9%), male sex (9.6), non-vegetarian diet (8.8%) and saturated fat intake (8.8%). The mean systolic as well as diastolic blood pressures were found to be higher among men, higher age groups, and in business occupation of the respondents. Conclusions : Despite treatment, most of the hypertensives had not achieved satisfactory control of blood pressure. Health education of the public is needed to control the various risk factors of hypertension.